MANAJEMEN STRATEGI DALAM EVALUASI SWOT UNTUK USAHA MIKRO, KECIL, DAN MENENGAH (UMKM): LITERATURE REVIEW - Ahmadi, Mirzam Arqy (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
The development of MSMEs in Indonesia is currently very rapid, various types of industry, both goods and MSME services, have spread widely in Indonesia. The increase in MSMEs is influenced by several factors, one of which is the superiority of MSMEs themselves. The important role given by MSMEs in national economic development and employment has made MSMEs increasingly advanced and developing today. As MSMEs develop, this will be accompanied by increased competition between one MSME and another. This means that business actors must implement strategic management to win global economic market competition. In this research the strategy is focused on SWOT analysis of MSMEs. SWOT analysis involves internal factors such as strengths and weaknesses as well as external factors such as opportunities and threats. The result of this research is that strategic management helps integrate SWOT evaluation results into concrete action plans, so that MSMEs can optimize resources, respond to environmental changes, and achieve sustainable business growth. Alignment between SWOT evaluation results and long-term business goals, a stakeholder-oriented approach, the use of information technology and analytics are key elements in achieving success for MSMEs in the complex and competitive era of globalization.